TECHNIQUES OF MINIMALLY INVASIVE SURGERY IN ADULT DEGENERATIVE SPINAL DEFORMITY : A SYSTEMATIC REVIEW - Davis Tionata, Nicholas; Dharma Kadar, Pranajaya (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Adult spinal deformities are a leading cause of pain and disability in the modern world. Advances in modern healthcare has allowed the population’s life expectancy to increase substantially. Despite this, there has been a marked increase in the number of ill and disabled individuals, leading to impairment in their quality of life. In order to continue performing successfully as an adult beyond retirement age, it is imperative to avoid pain and limitations in physical activity. When an adult develops a spinal deformity, surgery can help alleviate pain and reduce disability. Adult scoliosis is defined as a spine curvature greater than 10 degrees in a patient older than 18 years; nevertheless, in more severe cases, treatment is sometimes advised. Degeneration may be accelerated by asymmetric disk/facet degeneration or osteoporotic insufficiency fractures. Recently, minimally invasive spine surgery (MIS) has been at the forefront of innovation in spine surgery. MIS spine surgery not only refers to surgery through a smaller incision, but also to a technique that strives to reduce the approach-related morbidity associated with conventional open spine surgery. According to the findings of this study, Surgeons have to be prepared to offer both open or MIS for patients. Various MIS technique and its combination including hybrid surgery are used in cases of adult spinal deformity, the appropriate technique chosen for the surgery should include factors such as the spinopelvic harmony, age and outcome prediction of each patients into consideration as each technique has its own advantages and disadvantages.